Brucellosis concurrent with Johne's disease infection in a buffalo bull - Lim, Eric Teik Chung; Abdullah, Faez Firdaus Jesse; Bitrus, Asinamai Athliamai; Peter, Innocent Damudu; Azhar, Nur Amira; Thlama, Bura Paul; Hambali, Idris Umar; Mohd Lila, Mohd Azmi; Norsidin, Mohd Jefri (Nexus Academic Publishers, 2019)
This case report describes a veterinary clinical case of brucellosis concurrent with Johne’s disease in a buffalo bull that highlight the clinical and diagnostic management of the case. A 3-year-old Murrah buffalo bull weighing 250 kg with a body condition score of 2 out of 5 was presented with the primary complaint of decreasing body weight for the past one month. The most obvious signs observed during physical examinations were emaciation with prominent bony structures and enlargement of the scrotum. Upon palpation, the testicles were firm in consistency and warm. The differential diagnoses at that point of time were brucellosis, Johne’s disease, and Fascioliasis. The biochemical finding revealed hyperglobulinaemia (55.5 g/L) and the Rose Bengal Plate Test showed result of agglutination with the serum sample. Bacteriology finding demonstrated a positive result for acid-fast bacillus using the Ziehl-Neelsen’s stain method. Based on the history, physical examinations, and diagnosis work-ups, the buffalo bull was diagnosed infected with brucellosis concurrent with Johne’s disease infection. The prognosis of the case was grave and the animal was not treated due to the test-and-slaughter policy in Malaysia to control brucellosis. The farmer was advised to screen all animals on his farm as prevention and control for both diseases.